Biological and functional diversity of bird communities in natural and human modified habitats in Northern Flank of Knuckles Mountain Forest Range, Sri Lanka - KALYA SUBASINGHE; AMILA P. SUMANAPALA (Biodiversitas Journal of Biological Diversity, 2014)
Subasinghe K, Sumanapala AP. 2014. Biological and functional diversity of bird communities in natural and human modified habitats in Northern Flank of Knuckles Mountain Forest Range, Sri Lanka. Biodiversitas 15: 200-205. The Knuckles Mountain Forest Range(KMFR) has a complex mosaic of natural and human modified habitats and the contribution of these habitats to the biological andfunctional diversities has not been deeply studied. Present study investigated both of these diversities in five habitat types (two naturalhabitats: Sub-montane forest and Pitawala Patana grassland; three modified habitats: cardamom, pinus and abandoned tea plantations) inNorthern Flank of KMFR using birds as the indicator group. Bird communities were surveyed using point count method. A total of1,150 individuals belonging to 56 species were observed. The highest species richness was reported from the cardamom plantationwhere as sub-montane forest had the highest feeding guild diversity in terms of Shannon Weiner index. The abandoned tea plantationand the Pitawala Patana grasslands with fairly open habitats, showed relatively lower levels of feeding guild diversities. It is clear thatthe structurally complex habitats contribute more to the area’s biological and functional diversities and need to be taken into consideration when developing conservation plans.